Analysis of the influence of person organization fit and person job fit on turnover intention with work engagement as an intervening variable - Rida Astika Tamba; Nasution Nasution (Institute of Computer Science (IOCS), 2023)
The primary focus of academic and industrial interest has traditionally centered on the intentions behind employment turnover. This is crucial because if left unaddressed, the desire to leave a job can give rise to various issues within a company. This research aims to scrutinize and evaluate the effects of person-organization fit and person-job fit on turnover intention, incorporating work engagement as a mediating factor. The data were collected through a questionnaire distributed to 100 participants at Bhayangkara Hospital in Bengkulu City. Structural equation modeling (SEM) using the SmartPLS 3 (Partial Least Squares) program was employed for analysis. The study's findings reveal the following: there is a negligible and statistically insignificant correlation between person-organization fit and turnover intention, a similarly negligible and statistically insignificant correlation between person-job fit and turnover intention, a positive and significant correlation between person-organization fit and work engagement, a positive and significant correlation between person-job fit and work engagement, and a negative and significant impact of work engagement on turnover intention.